Affirmation of Student Identity Facing the Challenges of Islamic Education in the Era of Society 5.0 - Hastiani, Hastiani; Atika, Amelia; Rustam, Rustam; Naser, Muhammad Nikman; Rahmi, Nurul (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
The objective of this study is to affirm students’ self-identity through the implementation of biblio-consultation, which is informed by local wisdom, within the context of Islamic education. The concept of self-identity is reflected in the student’s sense of identity, which is inextricably linked to their regional cultural identity and forms a fundamental aspect of their national identity. The identity crisis experienced by students during the development of the contemporary era represents a significant challenge for the field of education. The transformation of local values in the contemporary era, if left unaddressed, may result in a loss of identity among students. An alternative solution would be to instill the values of local wisdom as an indigenous force within the region, thereby influencing the identity of the students. This research employs a qualitative hermeneutic approach. The objective of hermeneutics is to ascertain the underlying significance of a text and to conduct a comprehensive analysis of the intersubjective process. The research was conducted with the participation of several high school students in East Pontianak, with the objective of affirming their identity through the medium of bibliotherapy. The approach of biblio-counselling incorporates the values of local wisdom of Malay ethnicity and the use of stories that facilitate the students’ engagement with the situation and conditions they are reading about. The students engage in introspective reflection and the formulation of novel, constructive behavioural modifications. It is possible for students to possess a broad or global mindset while nevertheless exhibiting behaviours and manners that are consistent with Eastern cultural norms.